2013
DOI: 10.1371/journal.pone.0071257
|View full text |Cite
|
Sign up to set email alerts
|

Response of Copepods to Elevated pCO2 and Environmental Copper as Co-Stressors – A Multigenerational Study

Abstract: We examined the impacts of ocean acidification and copper as co-stressors on the reproduction and population level responses of the benthic copepod Tisbe battagliai across two generations. Naupliar production, growth, and cuticle elemental composition were determined for four pH values: 8.06 (control); 7.95; 7.82; 7.67, with copper addition to concentrations equivalent to those in benthic pore waters. An additive synergistic effect was observed; the decline in naupliar production was greater with added copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 75 publications
2
22
0
Order By: Relevance
“…However, while this maintenance of cellular homoeostasis allows acclimatization to environmental fluctuations, it comes with an energetic cost. Animals experiencing significant environmental changes must alter their energy distribution to accommodate these changes, and during unfavourable conditions, such alterations may ultimately subtract from the energy available for growth and reproduction (Stumpp et al, 2011;Fitzer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, while this maintenance of cellular homoeostasis allows acclimatization to environmental fluctuations, it comes with an energetic cost. Animals experiencing significant environmental changes must alter their energy distribution to accommodate these changes, and during unfavourable conditions, such alterations may ultimately subtract from the energy available for growth and reproduction (Stumpp et al, 2011;Fitzer et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal environment shape the physiological regulation of offspring, however, this maternal maintenance may change in fluctuating environment [ 44 ]. Offspring experiencing significant environmental changes may ultimately alter the energy for growth and reproduction [ 45 ]. We found that life history parameters of offspring, such as time to first brood, number of neonates at first clutch, body length and total population was impacted by maternal Ca, when raised on increased amount of M .…”
Section: Discussionmentioning
confidence: 99%
“…Adverse effects of Cu exposure in marine invertebrates include metabolic disruption, cytotoxicity, and neurotoxicity (Brown et al 2004;Lauer et al 2012). More specifically in copepods, Cu exposure may delay development and thus increase age at maturity (Sullivan et al 1983;Kwok et al 2008), reduce reproductive output (Reeve et al 1977;Fitzer et al 2013), and reduce foraging activity (Sharp and Stearns 1997).…”
Section: Introductionmentioning
confidence: 99%